Soil and organic carbon losses from varying land uses: a global meta‐analysis. (22nd April 2020) - Abdalla, Khatab; Mutema, Macdex; Hill, Trevor
Key insights: The key main finding from the study was that soil surface cover by vegetation and organic materials has the potential to significantly decrease the impact of key drivers of soil erosion processes such as rainfall and slope. Natural vegetation cover appeared more effective in terms of controlling erosion processes and enhancing ecosystem functionality of soils. The results also suggest that abandoning degraded agricultural lands might not be a sound option because the erosion processes might accelerate beyond control during the bare phase. Instead, soil cover practices such as the use of straw, manure, and even rock fragments should be encouraged. Abstract: Soil (SL) and organic carbon losses (SOCL ) have increased with human population and climate change linked extreme events. While SL and SOCL are clearly associated with surface run‐off, the impact of land use is still not well understood. This article elucidates the effects of land use, surface cover, and other environmental factors on SL and SOCL using data from 55 published studies. The overall SL (12.34 ± 2.25 Mg ha −1 year −1 ) and SOCL (21.80 ± 0.91 g C m −2 year −1 ) suggests substantial losses of the fertile topsoil globally. Grasslands (4.19 ± 1.22 Mg ha −1 year −1 ) had 77%, 66%, and 41% lower SL than orchards, croplands, and forests, respectively, which is attributable to higher soil organic matter and surface cover. Croplands had the highest SOCL at 22.78 ± 2.22 g C m −2 year −1 . Natural vegetation had 98% and 70% lower run‐off and SL than did plant residue mulched plots, indicating its great potential for surface run‐off and soil erosion control. Rainfall and slope were key drivers of soil erosion, while soil surface cover, SOC, and clay content decreased. These findings improve our knowledge on soil and organic carbon losses, which is useful for fostering sustainable management of soils and natural vegetation to enhance ecosystems functionality.